2012
DOI: 10.1039/c2ra21845c
|View full text |Cite
|
Sign up to set email alerts
|

Improving oxygen barrier and reducing moisture sensitivity of weak polyelectrolyte multilayer thin films with crosslinking

Abstract: Thin films of polyethylenimine (PEI) and poly(acrylic acid) (PAA), deposited using layer-by-layer assembly, were studied to understand the influence of various crosslinking methods on their oxygen and water vapor barrier. Glutaraldehyde (GA), 1-[3-(dimethylamino)propyl]-3-ethylcarbodiimide methiodide (EDC) and thermal crosslinking were evaluated with respect to film thickness and barrier properties. The thickness of an 8 bilayer PEI/PAA assembly decreased from 640 to 551 nm after crosslinking with a 0.1 M aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 69 publications
1
64
0
5
Order By: Relevance
“…An even further reduction in OTR resulted with heating the humidified film at 150 °C for 2 h, achieving an OTR of 0.08 cm 3 (m 2 d atm) −1 . The intention was to thermally crosslink the film, [30] but no contraction was observed (i.e., the film maintained a thickness of 1.99 ± 0.06 µm). Additionally, FTIR spectroscopy revealed no difference before and after heating, so it is likely that the heating simply removed water from the film.…”
Section: Resultsmentioning
confidence: 99%
“…An even further reduction in OTR resulted with heating the humidified film at 150 °C for 2 h, achieving an OTR of 0.08 cm 3 (m 2 d atm) −1 . The intention was to thermally crosslink the film, [30] but no contraction was observed (i.e., the film maintained a thickness of 1.99 ± 0.06 µm). Additionally, FTIR spectroscopy revealed no difference before and after heating, so it is likely that the heating simply removed water from the film.…”
Section: Resultsmentioning
confidence: 99%
“…PAH and PSS can form dense ionically‐crosslinked structures that compresses the thin film This densified structure imparts gas barrier. Many all‐polymer LbL films have been studied, using strong and weak polyelectrolytes, bio‐based polymers, and polyimide sheets, which all can form dense, ionically‐crosslinked structures. Yang et al found that PEI and PAA form exponentially growing, dense films with super gas barrier performance (<0.005 cm 3 m ‐2 day ‐1 atm ‐1 ) with just 8 BL .…”
Section: Layer‐by‐layer Assemblymentioning
confidence: 99%
“…However, the use of a plasticizer is normally required to achieve good mechanical properties (Rodriguez-Nuñez et al 2014). Another relevant limitation of chitosan films is their high hydrophilicity, which provokes changes in their physical aspect due to sorption of humidity from the environment (Yang et al 2012). To overcome this limitation, blends with hydrophobic polymers and multilayer films have been prepared (Suyatma et al 2004).…”
Section: Introductionmentioning
confidence: 99%